The Lovo Massif Rock Art (Democratic Republic of the Congo) - (:unkn) unknown (My University, 2014)
Unlike the Sahara or Southern Africa, the rock art of Central Africa is still largely unknown today. Despite being reported as early as the 16th century by Diego del Santissimo Sacramento, the rock art of the Kongo Central, an area encompassing parts of modern day Angola, Cabinda, the Republic of the Congo, Democratic Republic of the Congo, and Gabon, has never been widely researched and its age remains uncertain. Populated by the Ndibu, one of the Kongo subgroups, the Lovo massif is in the north of the ancient kingdom of Kongo. Even though this kingdom has, since 1500 AD, been one of the best documented in Africa, from historical sources as well as ethnographic and anthropological sources for the more recent periods, it remains largely unrecognized archaeologically. With 102 sites inventoried (including 16 ornate caves), it contains the largest concentration of rock art sites in the region, representing more than 5000 rock art images. Crossing ethnological, historical, archaeological and mythological points of view, this book illustrates that rock art played an important part in Kongo culture. Like historical sources or oral traditions, it can provide historians with important documentation and contribute significantly to the reconstruction of Africa's past.
Keywords: African Research